2013
DOI: 10.4028/www.scientific.net/amr.726-731.3883
|View full text |Cite
|
Sign up to set email alerts
|

Study on Soil Moisture Surrounding Coal Mining Subsidence Crack in Semi-Arid Region

Abstract: To provide theoretical basis for vegetation construction surrounding coal mining subsidence crack in semi-arid region, the focus of studying is on the soil moisture surroundings, the coal mining crack in different widths and soil moisture on different directions of a single crack. The result shows that the greater crack width is, the greater influence on soil moisture, the greater influence on deep soil moisture are. The standard deviations of soil moisture at each distance are crack width 0-20cm< width 20-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A simple sine model that describes the diurnal land surface temperature difference was established in this study. It has been widely reported that the diurnal cycles of land surface temperature and air temperature can be approximately described as sine curves ( Ma et al, 2013). Therefore, we assumed that both diurnal air temperature and land surface temperature are the sine functions of time t. , ) sin(…”
Section: Diurnal Land Surface Temperature Difference (∆T)mentioning
confidence: 99%
See 3 more Smart Citations
“…A simple sine model that describes the diurnal land surface temperature difference was established in this study. It has been widely reported that the diurnal cycles of land surface temperature and air temperature can be approximately described as sine curves ( Ma et al, 2013). Therefore, we assumed that both diurnal air temperature and land surface temperature are the sine functions of time t. , ) sin(…”
Section: Diurnal Land Surface Temperature Difference (∆T)mentioning
confidence: 99%
“…Coal energy consumption is significant in China and underground mining is the major practice of China's coal mining (Ma, 2013). Underground mining activities were reported to have caused many changes in the lithosphere, hydrosphere, atmosphere, biosphere and land cover at large spatial scales (Chen and Hu, 2004) and to have resulted in dramatic soil moisture changes in mining-led subsiding areas (Kong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This decrease would be significant in an area near ground fissures, which would influence infiltration by collecting the surface runoff (Peng, Wang, Cheng, & Lu, 2018). Therefore, the soil moisture in an area with ground fissures is commonly lower than that in an unmined area, as has been documented in previous research (Hu & Ceng, 2016;Ma, Gao, Zhang, Dong, & Huang, 2013). Furthermore, ground fissures were also found to result in the degradation of other soil properties, such as creating a loss of soil fertility, decrease in field capacity, and change in the soil microbial community (Ma, Zhang, Ruan, Guo, & Chai, 2019).…”
Section: The Long-term Effect Of Underground Mining On Vegetationmentioning
confidence: 84%